An Introduction to the Term Mushkil al-Qur’ān: اصطلاح مشکل القرآن :ایک تعارف - Mr. Samiullah; Dr. Muhammad Atif Aslam Rao (Corresponding Author), (Al-Mahdi Research Journal (MRJ), 2024)
The Qur’ān, being the literal word of God as revealed to Prophet Muhammad (peace be upon him), is considered the ultimate source of guidance for Muslims worldwide. However, its interpretation and understanding have been a subject of scholarly debate and inquiry throughout Islamic history. One of the significant concepts in Quranic exegesis is Mushkil al-Qur’ān, which refers to the ambiguous, obscure, or difficult-to-understand verses of the Qur’ān. This article aims to provide an introduction to the concept of Mushkil al-Qur’ān, exploring its definitions and classifications. A comprehensive review of the existing literature on the subject reveals that Muslim scholars and exegetes have employed various methods and approaches to interpret and explain the ambiguous verses of the Qur’ān. The article discusses the different types of Mushkil al-Qur’ān, including verses with unclear meanings, contradictory interpretations, and those requiring additional context for understanding. Furthermore, it examines the principles and guidelines established by Islamic scholars for dealing with such verses, ensuring that their interpretations remain consistent with the overall message and spirit of the Quran. By exploring the concept of Mushkil al-Qur’ān, this article seeks to contribute to a deeper understanding of Quranic exegesis and the ongoing scholarly efforts to uncover the meanings and implications of the Quranic text.